The nature of things: using the Earth with justice and charity - Kimmel, Meg, author; Davidson College, publisher (Colorado State University. Libraries, 2003)
Davidson College alumni journal story on Holmes Rolston winning the Templeton Prize and donating it to endow a chair in science and religion there. Holmes Rolston says he has spent his life in a lover's quarrel, not with his wife of four decades, but with the two disciplines he most loves: science and religion. Rolston recalls the influence of Davidson experiences in forming his career.
Keywords: Colorado State University; Templeton Prize; Davidson College; philosophy professor; Rolston, Holmes, 1932-2025